Optimization of Tensile-Shear Strength in the Dissimilar Joint of Zn-Coated Steel and Low Carbon Steel - Sukarman Sukarman; Amri Abdulah; Jatira Jatira; Dede Ardi Rajab; Rohman Rohman; Choirul Anwar; Yulfian Aminanda; Muhammad Ali Akbar (Automotive Experiences, 2020)
The present study features analytical and experimental results of optimizing resistance spot welding performed using a pneumatic force system (PFS). The optimization was performed to join SECC-AF (JIS G 3313) galvanized steel material with SPCC-SD low carbon steel. The SECC-AF is an SPCC-SD (JIS G 3141) sheet plate coated with zinc (Zn) with a thickness of about 2.5 microns. The zinc coating on the metal surface causes its weldability to decrease. This study aims to obtain the highest tensile-shear strength test results from the combination of the specified resistance spot welding parameters. The research method used the Taguchi method using four variables and a combination of experimental levels. The experimental levels are 2-levels for the first parameter and 3-levels for other parameters. The Taguchi optimization experimental results achieved the highest tensile-shear strength at 5049.64 N. It properly worked at 22 squeeze time cycles, 25 kA of welding current, and 0.6-second welding time and 12 holding-time cycles. The S/N ratio analysis found that the welding current had the most significant effect, followed by welding time, squeeze time, and holding time. The delta S/N ratio values were 1.05, 0.67, 0.57 and 0.29, respectively.